The madwoman in the attic : the woman writer and the nineteenth-century literary imagination - Gilbert, Sandra M. (Yale University Press, 1984)
A pathbreaking book of literary criticism is now reissued with a new introduction by Lisa Appignanesi that speaks to how The Madwoman in the Attic set the groundwork for subsequent generations of scholars writing about women writers, and why the book still feels fresh some four decades later.